Pelatihan Pembuatan Pupuk Organik Cair (POC) dan Eco-enzyme Solusi Alternatif Ramah Lingkungan di Desa Kledung Kecamatan Kledung Kabupaten Temanggung - Ainia, Muqodimatul; Syaifudin, Andang; Koniatussa'diyah, Koniatussa'diyah; Amalia Husna, Nafisatul; Widya Sri Utami, Yunita; Nurmey Laila Qotimah, Anjelia; Wahyu Wibowo, Satriya; Maulidya Nur Fauziah, Siti; Fawwaz Ramadian, Aditya; Nur Aidah, Ninda (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
One of the largest sources of waste in Indonesia is food waste, which is 39.81%. Various impacts occur if this continues to happen and no mitigation is carried out. The purpose of this activity is to provide training on how to make Liquid Organic Fertilizer (POC) and Eco-enzyme by utilizing organic waste from household food waste to minimize the accumulation of waste that can cause unpleasant odors. The methods used are seminars and direct training to the community. The results of this training increase the community's understanding and skills in processing organic waste into POC and Eco-enzyme products. Fermentation of organic waste from these two products was successful, indicated by low pH and appropriate color changes.